Análisis Técnico-Económico de una planta de conservas y sus posibilidades de reconversión para la producción de zumos ecológicos - Fernández Garcia, Yenia (Universidad Central "Marta Abreu" de las Villas, 2007)
The alimentary industry in the countries in development and among them Cuba requires, to cooperate to its competitiveness, besides being profitable, to have wide technologies , of conservation and prosecution of foods that consider the existent norms that govern the production of these and the requirements for the preservation of the environment. Starting present of this reality, an economic and technical study , of the present situation of a conserve plant of preserves in exploitation and an analysis of the possibilities of diversification of its technology in the conservation and prosecution of fruits, including the elaboration of juices. With this purpose a study of the technology installed in the plant was developed and a methodological procedure was applied to determine its profitability in the conservation and prosecution of the mango and the possibilities that the installation offers for its diversification with the production of mango juice, with the alimentary appropriate security and preservation of the environment. Of the obtained results we conclude that the installed technology is adapted technical and economically for the prosecution and conservation of the mango as marmalades, in an individual and integrated way to the conservation of other fruits and with a technology which permit the plant the possibilities of reconvertion for the production of juices of mangos and pineapple. To make the analysis of the actual plant and its reconvertion possibilities, the methodological procedure was used, derived of the application of the of the Complex Analysis of Processes techniques to the development and intensification of the Small and Medium Enterprescas of conservation (SME) and prosecution of foods. From the application of the methodological proposed procedure the following results were obtained: The installed technology is adapted as well as its technical state is adecuated allows diversifying the production, not only related with the conservation mediating sugary (marmalades) concentrate of different types of fruits, but also toward productions of mango juices and pineapple, with the addition of the previous coction stage and the use of the cooking (concentration of the product) operation in the pasteurization of the juice. As for the generation of steam, the existent capacity duplicates the present requirements, being able to use in the diversification of the production, with possibilities of electric cogeneration, with a favorable impact to the environment. The factory has the necessary water, so much for the prescrit productions, like to confront its diversification. A treatment system exists for residual liquids. It is had certified plantations of ecological mango in the region and of pineapple in process of certification that guarantee the production of supreme juice and concentrated ecological. It was proved that the plant is profitable for the present conditions so much with the integrated production of marmalades like of mango marmalade in the whole year. It is economically feasible the production of mango juice, not being this way that in pineapple for the studied conditions.

La industria alimentaria de los países en desarrollo y entre ellos Cuba requiere, para coadyuvar a su competitividad, además de ser rentable, contar con tecnologías multipropósito, de conservación y procesamiento de alimentos, que consideren las normas existentes que gobiernan la producción de estos y los requerimientos para la preservación del medio ambiente. Partiendo de esta realidad, se realizará un estudio técnico-económico de la situación actual de una planta de conservas en explotación y un análisis de las posibilidades de diversificación de su tecnología en la conservación y procesamiento de frutas, incluyendo la elaboración de zumos. Con este propósito se desarrolló un estudio de la tecnología instalada en la planta y se aplicó un procedimiento metodológico para determinar su rentabilidad en la conservación y procesamiento del mango y las posibilidades que ofrece la instalación para su diversificación con la producción de zumo de mango, con la adecuada seguridad alimentaria y preservación del medio. De los resultados obtenidos se concluye que la tecnología instalada es adecuada técnica y económicamente para el procesamiento y conservación del mango mediante mermeladas, de forma individual e integrada a la conservación de otras frutas y que la planta tiene posibilidades tecnológicas de reconversión para la producción de zumos de mangos y piña. Para efectuar el análisis de la planta actual y de sus posibilidades de reconversión se empleó el procedimiento metodológico, derivado de la aplicación de las técnicas del Análisis Complejo de Procesos al desarrollo e intensificación de las Pequeñas y Medianas Empresas (PYME) de conservación y procesamiento de alimentos. De la aplicación del procedimiento metodológico propuesto se obtuvieron los siguientes resultados: La tecnología instalada es adecuada así como su estado técnico y permite el diversificar la producción, no solamente relacionada con la conservación mediante concentrados azucarados (mermeladas) de diferentes tipos de frutas, sino también hacia producciones de zumos de mango y piña, con la adición de la etapa de precocción y la utilización de la operación de cocción (concentración del producto) en la pasteurización del zumo. En cuanto a la generación de vapor, la capacidad existente duplica los requerimientos actuales, pudiéndose emplear en la diversificación de la producción, con posibilidades de cogeneración eléctrica, con un impacto favorable al medio. La fábrica cuenta con el agua necesaria, tanto para las producciones actuales, como para afrontar su diversificación. Existe un sistema de tratamiento para residuales líquidos. Se cuenta con plantaciones certificadas de mango ecológico en la región y de piña en proceso de certificación, que garantizan la producción de sumos y concentrados ecológicos. Se comprobó que la planta es rentable para las condiciones actuales tanto con la producción integrada de mermeladas como de mermelada de mango en todo el año. Es económicamente factible la producción de zumo de mango, no siendo así el de piña para las condiciones estudiadas.
Keywords: Industria Alimenticia; Manipulación de Alimentos; Food Handling; Zumos; Juices; Planta de Conservas; Mangifera